2024
DOI: 10.1097/gox.0000000000005624
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Co-surgeon in Microvascular Breast Reconstruction: A Systematic Review and Meta-analysis

Joseph M. Escandón,
Andres Mascaro-Pankova,
Frank J. DellaCroce
et al.

Abstract: Summary: Using a co-surgeon model has been suggested to improve perioperative outcomes and reduce the risk of complications. Therefore, we evaluated if a co-surgeon model compared with a single microsurgeon model could decrease the surgical time, length of stay, rate of complications, and healthcare-associated costs in adult patients undergoing microvascular breast reconstruction (MBR). A comprehensive search was performed across PubMed MEDLINE, Embase, and Web of Science. Studies evaluating the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…We recognise the importance of experienced co-surgeons to facilitate simultaneous operating, reducing the operative time and thus optimising patient safety [ 17 ]. A recent meta-analysis by Escandón et al demonstrated the value of co-surgeon operators on operative time for autologous breast reconstruction, although they found surgical complications comparative compared to a single-surgeon approach [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recognise the importance of experienced co-surgeons to facilitate simultaneous operating, reducing the operative time and thus optimising patient safety [ 17 ]. A recent meta-analysis by Escandón et al demonstrated the value of co-surgeon operators on operative time for autologous breast reconstruction, although they found surgical complications comparative compared to a single-surgeon approach [ 18 ].…”
Section: Discussionmentioning
confidence: 99%